Flexible ureteroscopic lithotripsy with a suctioning ureteral access sheath for removing upper urinary calculi under local anesthesia - Zhang, Zhaolin; Leng, Song; Xie, Tianpeng; Yuan, Yuanhu; Wang, Xiaoning (Frontiers in Surgery, 2023)
Objectives: To probe the safety and effectiveness of flexible ureteroscopic lithotripsy (FURL) with a suctioning ureteral access sheath (S-UAS) for upper urinary calculi under local anesthesia (LA). Materials and Methods: The clinical data of 56 patients with upper urinary calculi treated by FURL with a S-UAS under LA from September 2019 to November 2022 were analyzed retrospectively. For LA, intramuscular Pethidine (1.0~2.0 mg/Kg) and Phenergan (25 mg) were administered 30 mins prior to surgery, oxybuprocaine hydrochloride gel was administered through the urethra at the beginning of surgery. The S-UAS and flexible ureteroscope were used for FURL. Demographic characteristics, stone related parameters and clinical outcomes were analyzed. Result: A total of 66 procedures were performed successfully, including 46 patients with unilateral operations (Group A) and 10 patients who underwent same-session bilateral operations (Group B). All 56 patients were operated on without changing the anesthesia strategy, and none required additional analgesia. The mean stone sizes of Group A and Group B were 20.24±5.45 mm and 29.40±3.89 mm. The mean operative times of the two groups were 53.04±13.35 mins and 90.00±15.81 mins, respectively. In Group A, the SFRs were 76.1% (35/46) and 85.1% (40/46) at postoperative Day 1 and Day 30, respectively. For Group B, the SFRs were 80.0% (16/20) and 85.0% (17/20), respectively. Four (8.7%) patients in Group A suffered complications including fever, stent pain, urosepsis, and steinstrasse. In Group B, one (10%) patient suffered from fever.